الفصل فی الملل والاہواء والنحل کے مصادر اور بیانِ مصادر میں علامہ ابن حزم کے مناہج کا تجزیاتی مطالعہ: An Analytical Study of the Sources of al-Fisal fi al-Milal wa al-Ahwa wa al-Nihal and Methodological Style of Ibn Hazm in revealing his sources of knowledge - Dr. Abid Naeem; Dr Nisar Ahmad; Janjua, Hafiz Muhammad Hamza (Al Manhal Research Journal, 2022)
Masadir (pl. of Masdar means sources and sources of knowledge) play very important role in determining the weightage as well as the status of any piece of writing in the field of knowledge. They help to find whether the writing falls in primary or secondary sources of the subject. When it comes to the sources of Islamic literature, it may include Quran, Hadith, Sirah, writings and letters of scholars of the field, meeting with scholars, observation, debates, studentship, direct and indirect narration etc. This article targets the sources of the famous book of Ibn Hazm, al Fisal fi al Milal wa al ahwa wa al nihal. Ibn Hazm has been proactive in narrating and critiquing the beliefs and other teachings of revealed as well as non-revealed religions and Muslim schools of thought. He had good knowledge about revealed religions of Judaism and Christianity, therefore he has employed religious terms from Hebrew and Latin religious texts. He had been generous in mentioning the sources of his knowledge on Judaism and Christianity. The sources of his information on non-revealed religions have not been unveiled by him. As far as the matter with his sources of information on Muslim schools of thought is concerned, he has revealed his sources for few ones and not revealed for few others.